Implementation of Learning Models to Improve Students English Language Abilities (LP2M, Institut Agama Islam Qamarul Huda, 2026)
This study examines the implementation of bilingual learning models in improving elementary school students’ English language abilities through a qualitative descriptive approach based on a literature review. The study analyzes 15 relevant journal articles published between 2014 and 2024, selected using criteria of relevance to bilingual learning, elementary education context, and empirical findings on language skill development. Data were analyzed using thematic analysis, including data reduction, categorization, and synthesis of recurring patterns across studies. The results reveal several consistent findings. First, bilingual learning implemented through translanguaging, gradual language exposure, and the integration of Indonesian (L1) and English (L2) significantly improves students’ listening and speaking skills. Second, interactive strategies such as games, songs, visual media, and guided speaking activities increase student participation, motivation, and confidence. Third, bilingual learning not only enhances linguistic competence but also contributes to cognitive development, including critical thinking, working memory, and cognitive flexibility. However, the effectiveness of implementation is influenced by teacher competence, availability of learning media, and variation in students’ initial abilities. The novelty of this study lies in providing a synthesized conceptual model of bilingual learning implementation that integrates linguistic, cognitive, and pedagogical dimensions within elementary education contexts. The findings imply that bilingual learning should be designed systematically through structured language transition, interactive strategies, and continuous teacher development. This study contributes to the development of bilingual learning theory, particularly in translanguaging practices, and offers practical guidance for teachers and curriculum developers in designing effective English learning in elementary schools.